One Psychology Profession, Many Standards: A Narrative Review of Training, Licensing, and Practice Standards and Their Implications for International Mobility - Tamaki Hosoda-Urban PhD; Makiko Watanabe PhD; Ellen H. O'Donnell PhD (SAGE Publishing, 2024)
This narrative review paper contrasts the professional prospects of psychologists in Japan and the U.S., discussing how divergent training, licensing, and practice standards appear to influence psychologists' profession in each country. Licensed psychologists in the U.S. practice with significant autonomy, which can be seen as a reflection of rigorous training requirements. In contrast, certified public psychologists in Japan complete a shorter-duration training regimen yet encounter more restrictive professional standards and greater financial challenges. These varying standards often create barriers to professional practice that impact psychologists on a global scale. Limited international mobility restricts opportunities for psychologists to learn abroad, exchange knowledge, and deliver culturally sensitive care to diverse populations, despite the need for such services among foreign individuals or immigrants in both countries. Furthermore, these disparities impede broader collaborative efforts to address global mental health challenges. Aligning training and licensing standards globally could enhance psychologists' international mobility, ensure consistent quality of care, and foster global collaboration. This alignment could improve access to culturally sensitive psychological services and help bridge the mental health care gap worldwide. This review emphasizes the necessity of further cross-cultural comparisons to understand the impact of training and licensing standards on clinical practice quality and accessibility. By presenting this comparative analysis, the study aims to inspire similar efforts, promoting global licensing reciprocity and the integration of professional psychology in an increasingly interconnected world.